Design and implementation of reconfigurable ASK and FSK modulation and demodulation algorithm on FPGA (Field Programmable Gate Array) - Md Wahid Sadiq; Md Ahasan Kabir (Sensors International, 2022)
Our modern world is completely driven by our ability to communicate all over the world with great precision, accuracy, and the least amount of time possible. Communication systems are used vastly in our worlds such as radar, aerospace, naval/maritime communication, underwater communication, mobile communication, or even in outer space such as satellite communication or space missions. Different communication system needs different types of modulation techniques. Design and implementation of reconfigurable modulators on cyclone-II FPGA (Field-programmable gate array) are proposed in this paper, wherein the type of modulations and demodulation can be dynamically reconfigured on the fly based on the requirement at any particular instance. The demodulator is intelligent enough to demodulate any modulated signal. FPGA or Field Programmable Gate Array is a computing device that can be programmed like CPU (Central Processing Unit) but fasted than CPU in parallel processing and DSP (Digital Signal Processing) related tasks. Consisting method of FPGA-based modulation does not support multiple modulation techniques at the same time and is not fast as they used Simulink-based simulation. This study has proposed FPGA based alternative to that, which can embody all the modulation techniques at once, making it way more versatile, cost-effective, and easy to use and test. The process begins with designing an algorithm. Then this algorithm has to be simulated. The algorithm is designed for both modulation and demodulation. In the modulation part, it is just simple logic to create different phrases and different frequencies of sinusoidal waves. But in demodulation, based on the frequency it can detect ASK (Amplitude Shift Keying) or FSK (Frequency Shift Keying) signal all by itself. Depending on the period of the signal, the algorithm can decide whether it is an ASK or FSK signal. After deciding it is an ASK of FSK signal, it starts to demodulate the signal. The outcome is, this FPGA-based modulator and demodulator are cheap, easy to configure, and can demodulate any type of demodulated signal. As it is reconfigurable, it's easy to deploy in any situation.